PENGARUH MOTIVASI, PENGEMBANGAN KARIR DAN KOMPENSASI TERHADAP KEPUASAN KERJA (Studi Pada Sales dan Marketing Departemen PT Soho Global Health Divisi Alliance di Pulau Jawa) - Achmat Riskiyono; Meita Pragiwani (Universitas Ichsan Sidenreng Rappang, 2025)
This study aims to determine the effect of motivation, career development, and compensation on job satisfaction in the sales and marketing department of PT Soho Global Health, Alliance Division, in Java. The strategy used in this study was an associative strategy using a survey method. The population of this study was all 60 employees working in the sales and marketing department of PT Soho Global Health, Alliance Division, in Java. The sample collection technique used a nonprobability sampling method with a saturated sampling technique, with a sample size of 60 employees. Data collection used a questionnaire that had been tested for outer and inner models. This study used the smartPLS program version 3.2.9 and Microsoft Excel. The results showed that the variables (1) motivation influenced job satisfaction, (2) career development influenced job satisfaction, and (3) compensation influenced job satisfaction.